Her Oxford - Batson, Judy G., 1943- (Vanderbilt University Press, 2008)
The 220 profiles of women who attended oxford between 1879 and 1960 constitute a Who's Who of women scientists, anthropologists, psychotherapists, educators, novelists, and social reformers in the English-speaking world.